HUBUNGAN METACOGNITIVE AWARENESS DENGANSELEFFICACY MAHASISWA BIDIKMISI JURUSAN PSIKOLOGI UNP - Anisya Fitri (Jurnal Riset Psikologi, 2018)
Abstract: Relationship Metacognitive Awareness with Self Efficacy Bidikmisi Student Psychology UNP. This study aims to find the relationship between metacognitive awareness with self efficacy in the Psychology Major FIPUniversity State of Padang. This type of research is a quantitative correlation.Research subjects amounted to 48 students bidikmisi force 2014-2016 in thePsychology Major FIP UNP. Method of sampling using purposive sampling. Thedata collection is done by using a scale of metacognitive awareness inventory and self efficacy. Data analysis using Product Moment Correlation Coefficient. The results showed a very significant positive relationship between the metacognitive awareness and self efficacy with rxy = 0,456 and p=0,011 and (p<0.05).Keywords: Self efficacy, metacognitive awareness, Bidikmisi studentsAbstrak: Hubungan antara Metacognitive Awareness dengan Self Efficacy pada Mahasiswa Bidikmisi Jurusan Psikologi Universitas Negeri Padang. Penelitian ini bertujuan untuk menemukan hubungan antara metacognitive awareness dengan self efficacy pada mahasiswa Bidikmisi Jurusan Psikologi Universitas Negeri Padang. Jenis penelitian ini ialah kuantitatif korelasional. Subjek penelitian berjumlah 30 orang mahasiswa Bidikmisi angkatan 2014-2016 di Jurusan Psikologi FIP UNP. Metode pengambilan sampel menggunakan teknik purposive sampling. Pengumpulan data dilakukan dengan menggunakan skala metacognitive awareness inventory dan self efficacy. Analisis data menggunakan Product Moment Correlation Coefisien. Hasil penelitian menunjukkan hubungan positif yang sangat signifikan metacognitive awareness dengan self efficacy dengan rxy=0,456 dan p=0,011 (p<0,05).Kata kunci: Self efficacy, metacognitive awareness, mahasiswa Bidikmisi